SiC whisker reinforced magnesium-based composite material and preparation method thereof

Through technical means such as high-energy ball milling and ultrasonic treatment, SiC whiskers are uniformly dispersed in the magnesium alloy matrix, solving the problem of uneven distribution of SiC reinforcement bodies, significantly improving the mechanical properties of magnesium-based composite materials and reducing costs.

CN119615021APending Publication Date: 2025-03-14NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411819813.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Among the existing SiC-reinforced magnesium-based composite materials, the SiC reinforcement has a low uniformity distribution in the magnesium alloy matrix, which affects the mechanical properties of the material.

Method used

SiCw-Zn composite powder was prepared by high-energy ball milling, and ultrasonic treatment was performed in the magnesium alloy melt. Combined with the hot extrusion process, the SiC whiskers were uniformly dispersed in the magnesium matrix.

Benefits of technology

The mechanical properties of magnesium-based composite materials are significantly improved, including tensile strength and yield strength, and the amount of alloy elements and SiC whiskers is added low, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615021A_ABST
    Figure CN119615021A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium-based composite materials, and discloses a SiC whisker reinforced magnesium-based composite material and a preparation method thereof. The SiC whisker reinforced magnesium-based composite material comprises a magnesium alloy matrix and a reinforcement body uniformly dispersed in the magnesium alloy matrix, the magnesium alloy matrix comprises the following elements in percentage by weight: 3wt% of Zn, 0.6 wt% of Nd, 0.5 wt% of Zr and the balance of Mg; the reinforcement is SiC whiskers, and the adding amount of the reinforcement is 0.4-0.7 wt% of the weight of the magnesium alloy matrix. The SiC whisker reinforced magnesium-based composite material disclosed by the invention has ultrahigh strength, and the addition amount of alloy elements and SiC whiskers is relatively low, so that the cost is greatly reduced; according to the preparation method, a strategy of combining alloying, compounding and hot extrusion is combined, the ultra-high-strength trace SiCw reinforced low-alloying magnesium-based composite material is prepared through a reinforcing mode of combining high-energy ball milling, hot extrusion and SiCw, the mechanical property of the magnesium-based composite material is greatly improved, the production cost is low, and the preparation method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of magnesium-based composite materials, and in particular to a SiC whisker reinforced magnesium-based composite material and a preparation method thereof. Background Art

[0002] Magnesium alloys have the advantages of low density, high specific strength, and high specific stiffness. They have significant effects in reducing the weight of vehicles and aircraft and improving fuel efficiency, which has aroused great interest from many researchers. However, the low absolute strength and poor room temperature properties of magnesium alloys limit their application. Improving the mechanical properties of magnesium alloys is a priority issue that needs to be solved in the long-term development of magnesium alloys.

[0003] Studies have shown that zinc can effectively reduce the stacking fault energy of Mg, promote the initiation of non-basal slip, and improve its plasticity; and Zn has a good aging strengthening effect in Mg. However, when the Zn content is greater than 4wt%, the plasticity will be significantly reduced, and the Mg-Zn alloy has a tendency to thermal cracking during casting, and the matrix structure is coarse. Therefore, other alloying elements are usually added to the Mg-Zn alloy to improve its microstructure. For example, adding a trace amount of zirconium (0.4wt% to 0.8wt%) to magnesium alloy can play a role in heterogeneous nucleation, thereby refining the magnesium alloy structure and improving the corrosion resistance and heat resistance of the alloy; in addition, introducing an appropriate amount of Nd element when smelting magnesium alloy can purify the melt, refine the grains, reduce the thermal tendency, improve the microstructure of the magnesium alloy, and can also improve the mechanical properties of the magnesium alloy by precipitation strengthening, solid solution strengthening and other means.

[0004] In addition, by adding ceramic reinforcements such as SiC reinforcements to prepare magnesium-based composites, their strength can be improved through two mechanisms: load transfer and thermal mismatch strengthening. The reinforcement structure can effectively determine the mechanical properties of the composite. Studies have shown that increasing the aspect ratio of the reinforcement can enhance the effectiveness of the load transfer mechanism, so the reinforcement effect of using whiskers as reinforcements is better than that of particles. In addition, the arrangement of whiskers also plays an important role in the strengthening of composites. Arranged whisker-reinforced metal-based composites produced by extrusion process show higher strength, especially in the extrusion direction.

[0005] However, in the existing SiC reinforced magnesium-based composites, the uniformity of the SiC reinforcement in the magnesium alloy matrix is ​​low, which greatly affects the mechanical properties of the material. Based on this, it is of great significance to develop high-strength SiC reinforced magnesium-based composites. Summary of the invention

[0006] The present application provides a SiC whisker reinforced magnesium-based composite material and a preparation method thereof, aiming to solve the problem of low strength of existing magnesium alloys and magnesium-based composite materials.

[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0008] In a first aspect of the present application, there is provided a SiC whisker reinforced magnesium-based composite material, which comprises a magnesium alloy matrix and a reinforcement uniformly dispersed in the magnesium alloy matrix;

[0009] The magnesium alloy matrix comprises the following elements in weight percentage: 3wt% Zn, 0.6wt% Nd, 0.5wt% Zr, and the balance Mg;

[0010] The reinforcement is SiC whisker, and the addition amount thereof is 0.4-0.7wt% of the weight of the magnesium alloy matrix.

[0011] Preferably, the length of the SiC whisker is 5 to 10 um, and the diameter is 100 to 200 nm.

[0012] In a second aspect of the present application, a method for preparing the above-mentioned SiC whisker reinforced magnesium-based composite material is provided, comprising:

[0013] S1, silicon carbide whiskers and Zn powder are treated by high-energy ball milling to obtain SiC w -Zn composite powder;

[0014] S2, prepare the raw materials of magnesium alloy matrix, melt Mg in protective atmosphere to obtain magnesium liquid, add Nd-containing raw materials and Zr-containing raw materials into the magnesium liquid, cool it to 550-600°C, and then add SiC w -Zn composite powder, heating to 680-700°C, ultrasonically treating and then casting to obtain a magnesium-based composite ingot;

[0015] S3, homogenizing the magnesium-based composite material ingot, and then hot extruding it to obtain a SiC whisker reinforced magnesium-based composite material.

[0016] Preferably, the high-energy ball milling is wet ball milling under an argon atmosphere, wherein the ball milling medium is anhydrous ethanol; the ball milling speed is 220 rpm, and the ball milling time is 20 h; wherein the ball mill rotates clockwise and counterclockwise alternately once every hour;

[0017] The amount of Zn powder used is 3% of the mass of the magnesium alloy matrix.

[0018] Preferably, the protective atmosphere in S2 is a mixed atmosphere of carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is 40:1.

[0019] Preferably, the Nd-clad raw material is Mg-30Nd alloy; and the Zr-clad raw material is Mg-30Zr alloy.

[0020] Preferably, SiC w-Zn composite powder is added to the magnesium alloy solution, specifically including:

[0021] SiC w -Zn composite powder is made into a volume of 1cm 3 The block is added into the semi-solid magnesium alloy melt by clockwise mechanical stirring. After the addition is completed, it is stirred counterclockwise for 10 minutes and the melting furnace temperature is increased to 680-700°C;

[0022] Among them, the stirring speed is 400-700r / min.

[0023] Preferably, during the ultrasonic treatment, the ultrasonic horn is positioned 2 cm below the liquid surface; the ultrasonic frequency is 25 kHz, the power is 3000 W, and the treatment time is 10 to 20 min;

[0024] The casting specifically includes: casting the magnesium alloy solution into a mold preheated to 400° C. and maintaining the pressure at 400 KN for 200 seconds.

[0025] Preferably, the homogenization treatment is specifically to keep the magnesium-based composite material ingot at 430° C. for 6 hours, heat it to 490° C. for 8 hours, and then water-cool it to room temperature.

[0026] Preferably, the hot extrusion temperature is 140° C., the extrusion ratio is 16:1, and the extrusion rate is 0.1 mm / s.

[0027] Compared with the prior art, the beneficial effects of this application are:

[0028] The SiC whisker reinforced magnesium-based composite material of the present application has ultra-high strength, which is significantly higher than the current commercial magnesium alloys and their composite materials, and the addition amount of alloy elements and SiC whiskers is low, which greatly reduces the cost.

[0029] This application combines the strategy of alloying, compounding and hot extrusion, through high-energy ball milling, hot extrusion and SiC w Combined strengthening method to prepare ultra-high strength trace SiC w Strengthening low alloy magnesium-based composite materials. The preparation method of the present application greatly improves the mechanical properties of magnesium-based composite materials, and has low production cost and is suitable for industrial production. w Whisker Preparation SiC w -Zn composite powder, SiC w -Zn composite powder is added to magnesium melt in a semi-solid state and ultrasonically treated to effectively open SiC w The agglomeration of SiC makes it dispersed evenly in the magnesium matrix, improving the mechanical properties of the magnesium-based composite material; wCombined with the addition of SiC w The whiskers are arranged along the extrusion direction, amplifying the effects of load transfer strengthening and thermal mismatch strengthening; on the other hand, the matrix grains can be refined by particle-stimulated nucleation and a high-density dislocations can be generated, amplifying the effects of grain boundary strengthening and dislocation strengthening, and further improving the mechanical properties of magnesium-based composites. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is a SEM image of the silicon carbide whiskers added in Example 1;

[0032] Figure 2 Schematic diagram of the extrusion process of the SiC whisker reinforced magnesium-based composite material of Example 1;

[0033] Figure 3 Schematic diagram of metallographic microstructure of SiC whisker reinforced magnesium-based composite material of Example 1 and Comparative Example 1;

[0034] Figure 4 The engineering stress-strain curves of the SiC whisker reinforced magnesium-based composite material of Example 1 and Comparative Example 1;

[0035] Figure 5 The SEM images of the SiC whisker reinforced magnesium-based composite materials prepared in Example 1, Comparative Example 2 and Comparative Example 3;

[0036] Figure 6 The engineering stress-strain curves of the SiC whisker reinforced magnesium-based composite materials prepared in Example 1, Comparative Example 2 and Comparative Example 3 are shown. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0038] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0039] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0040] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0042] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0043] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0044] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0045] In a first aspect, the present application provides a SiC whisker reinforced magnesium-based composite material, which comprises a magnesium alloy matrix and a reinforcement uniformly dispersed in the magnesium alloy matrix;

[0046] The magnesium alloy matrix comprises the following elements in weight percentage: 3wt% Zn, 0.6wt% Nd, 0.5wt% Zr, and the balance Mg;

[0047] The reinforcement is SiC whisker, and its addition amount is 0.4-0.7wt% of the weight of the magnesium alloy matrix. In the present application, it is preferred that the length of the SiC whisker is 5-10um and the diameter is 100-200nm.

[0048] The SiC whisker reinforced magnesium-based composite material of the present application has ultra-high strength, which is significantly higher than the current commercial magnesium alloys and their composite materials, and the addition amount of alloy elements and SiC whiskers is low, which greatly reduces the cost.

[0049] In a second aspect, a method for preparing the above-mentioned SiC whisker reinforced magnesium-based composite material is provided, comprising:

[0050] S1, silicon carbide whiskers and Zn powder are treated by high-energy ball milling to obtain SiC w -Zn composite powder;

[0051] In the present application, silicon carbide whiskers and Zn powder are added to a vacuum ball mill for wet grinding, and the ball milling medium is anhydrous ethanol; the ball milling is carried out under an argon atmosphere, the ball milling speed is 220 rpm, and the ball milling time is 20 hours. The ball mill rotates clockwise and counterclockwise alternately, once every hour; the ball milled product is vacuum dried to obtain SiC w -Zn composite powder. The present application uses high-energy ball milling to initially disperse the silicon carbide whiskers, which is beneficial for their uniform dispersion in the magnesium alloy matrix.

[0052] In the present application, the amount of SiC whiskers used is 0.4-0.7wt% of the weight of the magnesium alloy matrix; the amount of Zn powder used is 3% of the weight of the magnesium alloy matrix.

[0053] S2, prepare the raw materials of magnesium alloy matrix, melt Mg in protective atmosphere to obtain magnesium liquid, add Nd-containing raw materials and Zr-containing raw materials into the magnesium liquid, cool it to 550-600°C, and then add SiC w -Zn composite powder, heating to 680-700°C, ultrasonically treating and then casting to obtain a magnesium-based composite ingot;

[0054] In the present application, the protective atmosphere is a mixed atmosphere of carbon dioxide and sulfur hexafluoride, wherein the volume ratio of carbon dioxide to sulfur hexafluoride is 40:1.

[0055] The present invention heats and melts pure magnesium in a carbon dioxide and sulfur hexafluoride atmosphere, adds the required alloying elements (Nd-containing raw materials and Zr-containing raw materials), cools the temperature to 550-600°C, at which time the magnesium alloy is in a stable semi-solid state, and adds SiC w -Zn composite powder is made into a volume of 1cm 3 The block is added to the semi-solid magnesium alloy melt by clockwise mechanical stirring. After adding, it is stirred counterclockwise for 10 minutes at a stirring speed of 400-700r / min and the temperature of the smelting furnace is increased to 680-700℃ to melt the magnesium alloy into a liquid state. Subsequently, the ultrasonic amplitude transformer is set to 2cm below the liquid surface of the molten liquid, and the ultrasonic frequency is set to 25kHz and the power is set to 3000w for ultrasonic treatment for 10-20min, so that the silicon carbide whiskers are evenly distributed in the molten liquid. Subsequently, the molten liquid is cast into a mold preheated to 400℃, and the pressure is maintained at 400KN for 200s for die casting. After demolding, a magnesium-based composite ingot is obtained.

[0056] The present invention relates to the process of converting silicon carbide whiskers into SiC w -Zn is introduced into the magnesium alloy in the form of SiC and combined with ultrasonic treatment and die-casting process, which can effectively avoid the agglomeration of SiC whiskers and make them evenly dispersed in the magnesium alloy matrix, effectively improving the mechanical properties of the magnesium-based composite ingot.

[0057] S3, homogenizing the magnesium-based composite material ingot, and then hot extruding it to obtain a SiC whisker reinforced magnesium-based composite material.

[0058] In the present application, the magnesium-based composite material ingot is first cut into a specified size by wire cutting, and the cut magnesium-based composite material ingot is homogenized by keeping it at 430°C for 6 hours, then heating it to 490°C for 8 hours, and then cooling it to room temperature. The homogenized magnesium-based composite material ingot is then polished to remove the oxide scale, placed in a mold for heat preservation and hot extrusion to obtain a SiC whisker reinforced magnesium-based composite material.

[0059] Among them, extrusion temperature and extrusion rate have an important influence on magnesium-based composite materials. Hot extrusion can eliminate casting defects such as shrinkage and pores, and at the same time make SiC w distributed along the extrusion direction, thus providing a more effective load transfer strengthening effect. In addition, during the hot extrusion process, due to the w The incoordination with the deformation of the magnesium matrix leads to the w The high density of dislocations generated around the particles can, on the one hand, increase the degree of recrystallization of the magnesium matrix by stimulating nucleation through particles, thereby providing a stronger grain boundary strengthening effect; on the other hand, it can promote the precipitation of the second phase and enhance the Orowan strengthening effect.

[0060] In the present application, hot extrusion is preferably performed at a temperature of 140° C., with an extrusion ratio of 16:1 and an extrusion rate of 0.1 mm / s to obtain a SiC whisker reinforced magnesium-based composite material with the best mechanical properties.

[0061] This application combines the strategy of alloying, compounding and hot extrusion, through high-energy ball milling, hot extrusion and SiC w Combined strengthening method to prepare ultra-high strength trace SiC w Reinforced low-alloyed magnesium-based composite material. The preparation method of the present application greatly improves the mechanical properties of the magnesium-based composite material, has low production cost, and is suitable for industrial production.

[0062] The present application is further described below by way of examples.

[0063] Example 1

[0064] This embodiment provides a method for preparing a SiC whisker reinforced magnesium-based composite material, wherein the magnesium alloy matrix is ​​a Mg-3Zn-0.6Nd-0.5Zr alloy, and the reinforcement is a SiC whisker with a length of 5 to 10 μm and a diameter of 100 to 200 nm. The preparation method comprises:

[0065] S1, 5.5g of silicon carbide whiskers and 30g of Zn powder are subjected to high-energy ball milling in a zirconium oxide ball mill in an argon protective atmosphere. The ball milling medium is anhydrous ethanol, wherein the amount of SiC whiskers added is 0.5wt% of the mass of the magnesium alloy matrix, and the mass of Zn powder is 3wt% of the mass of the magnesium alloy matrix. The process of high-energy ball milling is: the ball milling speed is 220rpm, the ball milling time is 20h, and clockwise rotation and counterclockwise rotation are alternately performed every hour, with a rest period of 30min in between. After the ball milling is completed, the mixed liquid is allowed to stand and the upper clear liquid is poured out, and the mixture is placed in a vacuum drying oven and dried at 80°C to obtain SiC w -Zn composite powder.

[0066] S2, in a protective atmosphere of CO2 and SF6 (the volume ratio of CO2 to SF6 is 40:1), the melting furnace temperature is adjusted to 720°C, 1000g of pure magnesium is added, and after melting, 20g of Mg-30Nd and 17g of Mg-30Zr master alloy are added in sequence, and then the temperature is lowered to 550°C to make the magnesium alloy in a semi-solid state; then SiC w -Zn composite powder is wrapped in aluminum foil to form a 1cm 3 The block is added into the semi-solid magnesium alloy melt by clockwise mechanical stirring. After the composite powder is added, it is stirred counterclockwise for 10 minutes and the melting furnace temperature is increased to 700℃, and the stirring speed is 700r / min.

[0067] The magnesium-based composite material melt was subjected to high-power ultrasonic treatment, with the ultrasonic horn position being 2 cm below the liquid surface, the ultrasonic frequency being 25 kHz, the power being 3000 W, and the treatment time being 20 min. The magnesium-based composite material melt was then cast into a mold preheated at 400°C and maintained at a pressure of 400 KN for 200 s. After demolding, a magnesium-based composite material ingot was obtained.

[0068] S3, in a vacuum box electric furnace, the magnesium-based composite ingot is first kept at 430°C for 6 hours, then heated to 490°C for 8 hours, and then water-cooled to complete the homogenization treatment. The cast magnesium-based composite material after homogenization treatment is polished to remove the oxide scale, and then heated to 140°C in a mold, and hot extruded at an extrusion ratio of 16:1 and an extrusion rate of 0.1 mm / s to obtain a SiC whisker reinforced magnesium-based composite material.

[0069] Comparative Example 1

[0070] The difference between Comparative Example 1 and Example 1 is that there is no high-energy ball milling process. The preparation method thereof comprises:

[0071] S1, in the protective atmosphere of CO2 and SF6 (the volume ratio of CO2 to SF6 is 40:1), the temperature of the melting furnace is adjusted to 720℃, and Zn powder, Mg-30Nd and Mg-30Zr master alloys are added in sequence after the pure magnesium is melted, and then the temperature is lowered to 550℃ to make the magnesium alloy in a semi-solid state; then SiC w The powder is wrapped in aluminum foil to a size of 1 cm 3 The block is added into the semi-solid magnesium alloy melt by clockwise mechanical stirring. After the composite powder is added, it is stirred counterclockwise for 10 minutes and the melting furnace temperature is increased to 700℃, and the stirring speed is 700r / min.

[0072] The magnesium-based composite material melt was subjected to high-power ultrasonic treatment, with the ultrasonic horn position being 2 cm below the liquid surface, the ultrasonic frequency being 25 kHz, the power being 3000 W, and the treatment time being 20 min. The magnesium-based composite material melt was then cast into a mold preheated at 400°C and maintained at a pressure of 400 KN for 200 s. After demolding, a magnesium-based composite material ingot was obtained.

[0073] S2, in a vacuum box electric furnace, the magnesium-based composite ingot is first kept at 430°C for 6 hours, then heated to 490°C for 8 hours, and then water-cooled to complete the homogenization treatment. The cast magnesium-based composite material after homogenization treatment is polished to remove the oxide scale, and then heated to 140°C in a mold, and hot extruded at an extrusion ratio of 16:1 and an extrusion rate of 0.1mm / s to obtain a SiC whisker reinforced magnesium-based composite material.

[0074] Comparative Example 2

[0075] The difference between Comparative Example 2 and Example 1 is that the extrusion temperature in the hot extrusion process is different.

[0076] Steps S1 and S2 of Comparative Example 2 are the same as those of Example 1.

[0077] S3, in a vacuum box electric furnace, the magnesium-based composite ingot is first kept at 430°C for 6 hours, then heated to 490°C for 8 hours, and then water-cooled to complete the homogenization treatment. The cast magnesium-based composite material after homogenization treatment is polished to remove the oxide scale, and then heated to 180°C in a mold, and hot extruded at an extrusion ratio of 16:1 and an extrusion rate of 0.1 mm / s to obtain a SiC whisker reinforced magnesium-based composite material.

[0078] Comparative Example 3

[0079] The difference between Comparative Example 3 and Example 1 is that the extrusion rates in the hot extrusion process are different.

[0080] Steps S1 and S2 of Comparative Example 3 are the same as those of Example 1.

[0081] S3, in a vacuum box electric furnace, the magnesium-based composite ingot is first kept at 430°C for 6 hours, then heated to 490°C for 8 hours, and then water-cooled to complete the homogenization treatment. The cast magnesium-based composite material after homogenization treatment is polished to remove the oxide scale, and then heated to 140°C in a mold, and hot extruded at an extrusion ratio of 16:1 and an extrusion rate of 1mm / s to obtain a SiC whisker reinforced magnesium-based composite material.

[0082] Figure 1 This is a SEM image of the silicon carbide whiskers added in Example 1. Figure 1 It can be seen that the silicon carbide whiskers are free of impurities and have a good particle size; their average length is 5-10um and their diameter is 100-200nm.

[0083] Figure 2 Schematic diagram of the extrusion process of the SiC whisker reinforced magnesium-based composite material of Example 1. Figure 2 It can be seen that the silicon carbide whiskers SiC in the magnesium-based composite ingot w The whiskers are randomly distributed, and after hot extrusion, they are arranged along the extrusion direction. Due to the different rotation speeds of the whiskers in the extrusion direction, the extrusion stress is unevenly distributed along each whisker, generating residual stress and strain in the matrix. The matrix around the whiskers and the whisker deformation are not coordinated, which leads to the generation of a large number of dislocations. The generated dislocations provide the necessary energy for the occurrence of dynamic recrystallization of the magnesium matrix and promote the refinement of grains.

[0084] Figure 3 Schematic diagram of the metallographic microstructure of the SiC whisker reinforced magnesium-based composite material of Example 1 and Comparative Example 1, wherein Figure 3(a) is the SiC whisker reinforced magnesium-based composite material of Example 1, Figure 3 (b) is the SiC whisker reinforced magnesium-based composite material of Comparative Example 1. Figure 3 It can be seen that compared with the SiC whisker reinforced magnesium-based composite material prepared by the method without high-energy ball milling in Comparative Example 1, the SiC whisker reinforced magnesium-based composite material of Example 1 has a more uniform microstructure. The reason is that the present application uses high-energy ball milling to make the silicon carbide whiskers preliminarily dispersed; w The introduction of -Zn into magnesium alloys can effectively prevent the agglomeration of silicon carbide whiskers, facilitate their uniform dispersion in the magnesium alloy matrix, and effectively improve the mechanical properties of magnesium-based composite ingots.

[0085] Figure 4 Figure 1 is an engineering stress-strain curve of the SiC whisker reinforced magnesium-based composite material of Example 1 and Comparative Example 1. Figure 4 It can be seen that the tensile strength, yield strength and elongation of the SiC whisker reinforced magnesium-based composite material prepared in Example 1 are significantly higher than those of the SiC whisker reinforced magnesium-based composite material prepared in Comparative Example 1. The yield strength of the composite material prepared in Example 1 is 443.5 MPa, the tensile strength is 544.8 MPa, and the elongation is 4.3%. Compared with the yield strength and tensile strength of the SiC whisker reinforced magnesium-based composite material in Comparative Example 1, they are increased by 133.2 MPa and 120.3 MPa, respectively, and the elongation is increased by 105%.

[0086] Figure 5 The SEM images of the SiC whisker reinforced magnesium-based composite materials prepared in Example 1, Comparative Example 2 and Comparative Example 3 are shown. Figure 5 (a) is the SiC whisker reinforced magnesium-based composite material prepared in Example 1, with an extrusion temperature of 140° C. and an extrusion rate of 0.1 mm / s; Figure 5 (b) is the SiC whisker reinforced magnesium-based composite material prepared in Comparative Example 2, wherein the extrusion temperature is 180° C. and the extrusion rate is 0.1 mm / s; Figure 5 (c) is the SiC whisker reinforced magnesium-based composite material prepared in Comparative Example 3, with an extrusion temperature of 140°C and an extrusion rate of 1 mm / s. Figure 5 It can be seen that the SiC whisker reinforced magnesium-based composite material prepared in Example 1 has the finest grain size and precipitate phase size, and the volume fraction of the precipitate phase is the highest; the SiC whisker reinforced magnesium-based composite material prepared in Comparative Example 2 is second, and the SiC whisker reinforced magnesium-based composite material prepared in Comparative Example 3 has the largest grain size and only a very small amount of precipitate phase.

[0087] Compared with Comparative Example 2, as the extrusion temperature increases, the diffusion capacity of grain boundaries and elements is enhanced in Example 1, resulting in the growth of grain size and precipitated phase; on the other hand, as the extrusion temperature increases, the deformation incompatibility between the whiskers and the matrix decreases, resulting in a decrease in the internal distortion energy of the material, which reduces the nucleation driving force of the precipitated phase and thus reduces the volume fraction of the precipitated phase. Compared with Comparative Example 3, as the extrusion rate increases, a large amount of extrusion heat is generated in Example 1, resulting in the growth of grains; and the faster extrusion rate causes the second phase to not have time to precipitate, which greatly reduces the precipitated phase inside the material. In addition, as the extrusion speed increases, the degree of fracture of the whiskers increases, which will have a negative effect on the whisker strengthening effect and matrix toughness.

[0088] Figure 6 The engineering stress-strain curves of the SiC whisker reinforced magnesium-based composite materials prepared in Example 1, Comparative Example 2 and Comparative Example 3 are shown.

[0089] from Figure 6 It can be seen that the SiC whisker reinforced magnesium-based composite material prepared in Example 1 (hot extrusion temperature 140°C, extrusion rate 0.1 mm / s) exhibits the highest tensile strength of 544.8 MPa and yield strength of 443.5 MPa; the main reasons are: first, the grain boundary strengthening effect caused by grain refinement is the most significant; second, it has the finest precipitate phase scale and the highest volume fraction, resulting in a significant improvement in the orowan strengthening effect; third, under the preparation process of Example 1, the whiskers maintain a high integrity and a high load transfer strengthening effect.

[0090] The SiC whisker reinforced magnesium-based composite material prepared in Comparative Example 2 (hot extrusion temperature 180°C, extrusion rate 0.1 mm / s) has the highest elongation of 6.3%. This is because the increase in extrusion temperature leads to a decrease in the incompatibility between the whiskers and the matrix, and the internal distortion of the material can be reduced, thereby allowing the material to maintain a higher elongation.

[0091] The mechanical properties of the SiC whisker-reinforced magnesium-based composite material prepared in Comparative Example 3 (hot extrusion temperature 140°C, extrusion rate 1mm / s) are the worst. This is because the grain size of the material produced by this process is relatively coarse, and on the other hand, the material has a very small amount of precipitated phase, which reduces the Orowan strengthening effect; in addition, the degree of whisker fracture is aggravated under this process, resulting in a reduction in the whisker load transfer strengthening effect, and at the same time, the crack propagation is aggravated, resulting in a significant reduction in the toughness of the material.

[0092] The SiC whisker reinforced magnesium-based composite material prepared in Example 1 of the present application has ultra-high strength, which is significantly higher than current commercial magnesium alloys and their composite materials, and has the best mechanical properties.

[0093] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A SiC whisker reinforced magnesium-based composite material, characterized in that: It includes a magnesium alloy matrix and a reinforcement uniformly dispersed in the magnesium alloy matrix; The magnesium alloy matrix comprises the following elements in weight percentage: 3wt% Zn, 0.6wt% Nd, 0.5wt% Zr, and the balance Mg; The reinforcement is SiC whisker, and the addition amount thereof is 0.4-0.7wt% of the weight of the magnesium alloy matrix.

2. The SiC whisker reinforced magnesium-based composite material according to claim 1, characterized in that: The length of the SiC whisker is 5-10 um, and the diameter is 100-200 nm.

3. The method for preparing the SiC whisker reinforced magnesium-based composite material according to claim 1, characterized in that: include: S1, silicon carbide whiskers and Zn powder are treated by high-energy ball milling to obtain SiC w -Zn composite powder; S2, prepare the raw materials of magnesium alloy matrix, melt Mg in protective atmosphere to obtain magnesium liquid, add Nd-containing raw materials and Zr-containing raw materials into the magnesium liquid, cool it to 550-600°C, and then add SiC w -Zn composite powder, heating to 680-700°C, ultrasonically treating and then casting to obtain a magnesium-based composite ingot; S3, homogenizing the magnesium-based composite material ingot, and then hot extruding it to obtain a SiC whisker reinforced magnesium-based composite material.

4. The preparation method according to claim 3, characterized in that: The high-energy ball milling is a wet ball milling under an argon atmosphere, wherein the ball milling medium is anhydrous ethanol; the ball milling speed is 220 rpm, and the ball milling time is 20 hours; wherein the ball mill rotates clockwise and counterclockwise alternately once every hour; The amount of Zn powder used is 3% of the mass of the magnesium alloy matrix.

5. The preparation method according to claim 3, characterized in that: The protective atmosphere in S2 is a mixed atmosphere of carbon dioxide and sulfur hexafluoride, and the volume ratio of carbon dioxide to sulfur hexafluoride is 40:

1.

6. The preparation method according to claim 3, characterized in that: The Nd-clad raw material is Mg-30Nd alloy; the Zr-clad raw material is Mg-30Zr alloy.

7. The preparation method according to claim 3, characterized in that: SiC w -Zn composite powder is added to the magnesium alloy solution, specifically including: SiC w -Zn composite powder is made into a volume of 1cm 3 The block is added into the semi-solid magnesium alloy melt by clockwise mechanical stirring. After the addition is completed, it is stirred counterclockwise for 10 minutes and the melting furnace temperature is increased to 680-700°C. Among them, the stirring speed is 400-700r / min.

8. The preparation method according to claim 3, characterized in that: During the ultrasonic treatment, the ultrasonic horn is positioned 2 cm below the liquid surface; the ultrasonic frequency is 25 kHz, the power is 3000 W, and the treatment time is 10 to 20 min; The casting specifically includes: casting the magnesium alloy solution into a mold preheated to 400° C. and maintaining the pressure at 400 KN for 200 seconds.

9. The preparation method according to claim 3, characterized in that: Specifically, the homogenization treatment is to keep the magnesium-based composite material ingot at 430° C. for 6 hours, heat it to 490° C. for 8 hours, and then cool it to room temperature with water.

10. The preparation method according to claim 3, characterized in that: The hot extrusion temperature is 140° C., the extrusion ratio is 16:1, and the extrusion rate is 0.1 mm / s.